Training the Professionals that Industry Needs: The Digital Software Engineering Education Program at PUC-Rio - Kalinowski, Marcos; Escovedo, Tatiana; Pina, Fernanda; Vidal, Adriana; Silva, Ariane Pereira Da; Ponsirenas, Ricardo; Rocha, Daiana Garibaldi Da (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2023)
Software is strategic for Brazil’s development, but the lack of a larger qualified workforce limits the country’s productive capacity. This paper reports the experience of deploying a large-scale distance learning education program to meet the practical needs of the software industry. We applied design thinking involving software engineering and continued education experts of PUC-Rio and an external consultancy to design a methodology that we consider ideal, including learning objects hitherto not used in continued education in Brazil. The key elements of the conceived methodology include (i) the organization of the course in Sprints that involve the elaboration in practice, with synchronous and asynchronous assistance, of Minimum Viable Products (MVPs) that evaluate learning hypotheses associated with the disciplines; (ii) premium materials with innovative learning objects co-created by professors that have theoretical depth and project experience in their subject areas and professional instruction designers; and (iii) industry integration through React videos and synchronous meetings with reference professionals. We conducted a pilot study implementing the methodology for one discipline and gathering feedback from stakeholders. After validating and adjusting the methodology, the professional education program was launched in February 2023 and by July of that same year it already had more than 300 students from all over Brazil. Most students successfully developed their MVPs, integrating them into their professional portfolio and demonstrating the acquired expertise. The students’ satisfaction with the methodology is widely and easily evidenced. The digital Software Engineering education program of PUC-Rio is now a reality and is helping prepare the future workforce for the software area; we share the experience and lessons learned with the community.